POTENSI EKOENZIM DARI LIMBAH ORGANIK UNTUK MENINGKATKAN PRODUKTIVITAS TANAMAN - Najla Lubis; M. Wasito; Siti Tri Ananda, Hasril Wahyudi (PROSEDING, 2022)
Ecoenzyme (EE) is a fermented organic waste solution derived from fruits and vegetables. The goal of this research is to see how ecoenzymes affect plant development and production, specifically in the edamame soybean plant (Glycine max L. Merill). This study used a non-factorial randomized block design (RBD) with four treatments and five blocks for a total of twenty research plots. EE, which was dissolved in water in a certain ratio, was investigated. E0 = without giving EE, E1 = 1: 100, E2 = 1:200, and E3 = 1: 300 were the four stages of the research treatment (EE: water). Plant height (cm), number of pods per sample (pods), number of pods per plot (pods), weight of sample pods (g), and weight of plot pods were all measured (g). The results of the statistically analyzed research show that ecoenzymes has no significant influence on all of the examined parameters, the best result is E1. The nitrogen content of the soil was determined using the Kjeldahl test method, while the P, K, CaO, MgO, and Fe elements were determined using the Atomic Absorption Spectrophotometric (AAS) method, where there was an increase in the nutrients N, K, Ca, and Mg. Keywords : ecoenzymes, fruits and vegetables fermented, organic waste